Pola Asuh Orang Tua Dalam Penggunaan Smartphone Pada Anak Sekolah Dasar - Fahmi Naufal Alwie; Ika Oktavianti; Erik Aditia Ismaya (WASIS : Jurnal Ilmiah Pendidikan, 2023)
The purpose of the research was to analyze the parenting style applied by parents to the use of smartphones in children in the village of Ngaluran. The method used was a qualitative case study.The research was conducted in the Village of Ngaluran Dukuh Kalitekuk RT04 RW02 Karanganyar District, Demak Regency. The time for conducting the research was January 2023. The main informants of the research were the parents of children who lived around RT 04 RW 02. Data collection techniques included observation, interviews and documentation. The data validity test includes credibility, transferability, reliability, confirmability tests. Research data analysis techniques were carried out by means of data reduction, data presentation, and drawing conclusions.The results of the research conducted show that on average parents in the village of Ngaluran in providing parenting patterns to children use democratic parenting. The role of such parenting styles can have a positive impact on the use of smartphones in children and improve the growth and development of children so that children can increase their knowledge, expand their network of friendships, and facilitate communication.